Pierre and His People: Tales of the Far North. Volume 5. - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pierre and His People: Tales of the Far North. Volume 5" by Gilbert Parker is a collection of short stories written during the early 20th century. The book encapsulates the rich tapestry of life in the Canadian North, exploring themes of love, sacrifice, hardship, and the human spirit against a backdrop of challenging landscapes. The tales weave in the trials and tribulations of various characters, bringing forth the beauty and brutality of life in this remote region. The stories within the collection feature a range of characters, including Antoine and Angelique, who guard a precious mine while confronting the encroaching isolation of winter and their deep fears. In another tale, Hilton encounters Ida, a deaf-mute girl, and navigates their unspoken bond as he grapples with societal expectations. "A Tragedy of Nobodies" delves into the complexities of love and loss, illustrating the harsh realities faced by women in rough frontier settlements, particularly through the character Blanche. Lastly, "A Sanctuary of the Plains" follows Father Corraine as he shelters a wounded outlaw, leading to a profound confrontation with morality and redemption. Through each narrative, Parker captures the resilience of his characters in the face of both external and internal struggles, inviting readers to explore the depths of human emotion amidst the beauty of the Far North. (This is an automatically generated summary.)
Antoine and Angelique -- The cipher -- A tragedy of nobodies -- A sanctuary of the plains.
Release date is 2004-07-01
This eBook was produced by David Widger
Keywords: Canada, Northern -- Fiction; Short stories, Canadian